Laser polishing of selective laser melted components. (August 2015) - Marimuthu, S.; Triantaphyllou, A.; Antar, M.; Wimpenny, D.; Morton, H.; Beard, M.
Abstract: The shape complexities of aerospace components are continuously increasing, which encourages industries to refine their manufacturing processes. Among such processes, the selective laser melting (SLM) process is becoming an economical and energy efficient alternative to conventional manufacturing processes. However, dependant on the component shape, the high surface roughness observed with SLM parts can affect the surface integrity and geometric tolerances of the manufactured components. To account for this, laser polishing of SLM components is emerging as a viable process to achieve high-quality surfaces. This report details an investigation carried out to understand the basic fundamentals of continuous wave laser polishing of SLM samples. A numerical model, based on a computational fluid dynamic formulation, was used to assist the understanding of melt pool dynamics, which significantly controls the final surface roughness. The investigation identified the input thermal energy as the key parameter that significantly affect the melt pool convection, and essentially controls the surface quality. Minimum meltpool velocity is essential to achieve wider laser polished track width with good surface finish. Experimental results showed a reduction of surface roughness from 10.2 μm to 2.4 μm after laser polishing with optimised parameters. Strategies to control the surface topology during laser polishing of SLM components are discussed. Highlights: Experimental and theoretical calculations were used to understand laser polishing process. No evidence of alpha case formation or thermal cracking. Effect of laser energy on surface roughness and microstructure is discussed. In laser polishing, melt pool velocity significantly affects the surface roughness. Increased input energy result in increased meltpool velocity and high surface roughness.